Slaves and religions in Graeco-Roman antiquity and modern Brazil - Hodkinson, Stephen; Geary, Dick. (Newcastle upon Tyne, UK : Cambridge Scholars Publishing, 2012)
Slaves have never been mere passive victims of slavery. Typically, they have responded with ingenuity to their violent separation from their native societies, using a variety of strategies to create new social networks and cultures. Religion has been a ma
Description based on print version record.
Keywords: Slavery -- Greece -- Religious aspects; Slavery -- Rome -- Religious aspects; Slavery -- Brazil -- Religious aspects; SOCIAL SCIENCE / Slavery; Electronic books